ChemInform Abstract: Small Inorganic Rings in the 21st Century: From Fleeting Intermediates to Novel Isolable Entities. Issue 41 (7th October 2014) - He, Gang; Shynkaruk, Olena; Lui, Melanie W.; Rivard, Eric
Abstract Review: 846 refs.